Uma hermenêutica bíblica popular e feminista na perspectiva da mulher nordestina: um relato de experiência - Santos, Odja Barros (2010)
The main goal of this dissertation is to consider the pedagogical, methodological and hermeneutical implications of the reading of the Bible, in a popular and feminist perspective. In the first two chapters are presented some implications involved in this reading. Concerning the pedagogical implications we came back to some ideas on liberating education of Paulo Freire‟s work Pedagogy of the oppressed. Concerning the methodological implications we highlighted in the popular reading of the Bible as a reference for true popular Bible study process, starting from a liberating and empowering pedagogy. Concerning the hermeneutical implications, it was proposed a dialogue with the critical feminist liberation hermeneutics, developed by Elisabeth S. Fiorenza, because of her political and ethical commitment with women while historical subjects. In the third chapter are presented a report of the Flor de Manacá group experience, and the reflection conducted by that group on the text of the Gospel of John 8.1-12. It aimed not only to show the popular methodology and feminist reading of the Bible, but also the whole process of the group as a subject of the reading of the Bible in the context of Brazilian Northeastern culture. This experience and research reveal the importance of the groups and of the community in a process of a new pedagogy for biblical studies, committed to a reading of the Bible that is liberating and empowering and, at the same time, sensible to the cultural context in which it is inserted.